Human T cell immunosenescence and inflammation in aging - Bektas, Arsun; Schurman, Shepherd H.; Sen, Ranjan; Ferrucci, Luigi (Journal of leukocyte biology, 2017)
Review of the origin of the mild proinflammatory state that characterizes many older individuals, with a focus on changes in T cell function over time. The aging process is driven by a finite number of inter‐related mechanisms that ultimately lead to the emergence of characteristic phenotypes, including increased susceptibility to multiple chronic diseases, disability, and death. New assays and analytical tools have become available that start to unravel some of these mechanisms. A prevailing view is that aging leads to an imbalance between stressors and stress‐buffering mechanisms that causes loss of compensatory reserve and accumulation of unrepaired damage. Central to this paradigm are changes in the immune system and the chronic low‐grade proinflammatory state that affect many older individuals, even when they are apparently healthy and free of risk factors. Independent of chronological age, high circulating levels of proinflammatory markers are associated with a high risk of multiple adverse health outcomes in older persons. In this review, we discuss current theories about causes and consequences of the proinflammatory state of aging, with a focus on changes in T cell function. We examine the role of NF‐κB activation and its dysregulation and how NF‐κB activity differs among subgroups of T cells. We explore emerging hypotheses about immunosenescence and changes in T cell behavior with age, including consideration of the T cell antigen receptor and regulatory T cells (Tregs). We conclude by illustrating how research using advanced technology is uncovering clues at the core of inflammation and aging. Some of the preliminary work in this field is already improving our understanding of the complex mechanisms by which immunosenescence of T cells is intertwined during human aging.